A Brief Glance at the Diversity of Applications of Islamic Law in Society - Bisri, Hasan (Tsamratul Fikri, 2024)
This essay aims to elucidate and examine the intricacies of cognition and the wide range of implementations (tathbîq) of Islamic jurisprudence. The author's research concluded that the dynamics of Islamic legal thinking arise from the inherent limitations of human understanding in comprehending the intentions of Allah and His Messenger. Hence, the author advocates for the significance of engaging in ongoing dialogues to pursue the ultimate truth and obtain divine validation. This study aims to raise awareness among Muslims about the significant influence of social, political, economic, and cultural factors on the implementation of Islamic law in society.